Verification of the mechanism and effect of secondary advanced dewatering promoted by selective oxidative decomposition: On pilot scale. Issue 2 (April 2022) - Lin, Naixi; Zhu, Wei; You, Xingyu; Wang, Xin; Zhong, Jun; Sun, Jipeng; Sun, Tianyang; Cao, Jun; Li, Lei
Abstract: In the sewage treatment industry of China, there is a huge market demand for direct secondary advanced dewatering technology to reduce the water content of municipal dewatered sludge from approximately 80% to below 60%. In this study, three typical oxidants (Fenton's reagent, H2 O2 and KMnO4 ) were applied to pre-treat dewatered sludge, which was then dewatered further using a PFFP we manufactured on pilot-scale. Only high-dose H2 O2 and Fenton's reagent gave flow values of 4.5 cm and ratios of free water/ (dry matter + bound water) of greater than 1.1, which allowed for successful transfer of dewatered sludge into the chambers by a diaphragm pump. The dewatering mechanism involved injection and squeezing of the dewatered sludge which was not exactly similar to that of concentrated sludge. The overall advanced dewatering performance was improved after conversion of bound water to free water. The final moisture content was less than 50% under the optimal conditions when the Fenton's reagent dose was 2257 mol/t·db. The reaction of less oxidizing other biomass and intensively selective oxidizing polysaccharide was also verified in our experiment. Graphical Abstract: The conversion of bound water to free water in dewatered sludge could be promoted by the selective oxidative decomposition of polysaccharides after the pre-treatment of Fenton's reagent. The increasing free water improves the injection and overall direct secondary dewatering performance in a plate-and-frame filter press on pilot scale. After the operation, dewatered sludge (water content of 80%) could be divided into half cake (water content of below 60%) and half tail-water. ga1 Highlights: Direct secondary advanced dewatering technology for dewatered sludge could be realized. Material composition determining fluidity required in injection is free water/ (dry matter + bound water) larger than 1.1. Overall advanced dewatering performance increases though the conversion of bound water to free water. The mechanism of selective oxidative decomposition of polysaccharides is verified on pilot-scale.